Enhancing Vocabulary Mastery through the Use of Educandy Game Application as an Interactive Learning Tool - Aenurrifah, Ahmad Aunilah; Widhiyanto; TRISANTI, NOVIA (Universitas Negeri Semarang, 2025)
Currently, there is growing integration on the use of technology. There should be appropriate tools to enhance vocabulary mastery for the learners, especially English learners. Educandy is recognized as an interactive learning platform to support learners' vocabulary mastery. This study adopted a mixed-method approach to provide a more comprehensive understanding by examining both learning outcomes and students’ responses. Its aim is to provide insights into how Educandy can enhance vocabulary learning among seventh-grade students at MTs Arrobiah Azzain Grinting. 60 students were randomly selected and divided into two groups; experimental and control groups. Educandy has improved vocabulary at MTs Arrobiah Azzain, shown by higher post-test scores and positive student feedback from observations and interviews. This finding confirmed that using the Educandy video game effectively enhanced EFL secondary students’ vocabulary acquisition. The implementation of this interactive tool not only improved students’ vocabulary knowledge but also increased their enthusiasm for learning. The students were able to enjoy learning vocabulary using Educandy video game, which made them enthusiastic in learning. The students could easily remember what they have learned in their class by using Educandy video game. Based on the research findings, it was concluded that using the Educandy video game effectively enhanced vocabulary learning for EFL secondary students. This was evident that there was improvement in students’ vocabulary mastery and their increased enthusiasm for learning.